CCL3 and CXCL12 production in vitro by dental pulp fibroblasts from permanent and deciduous teeth stimulated by Porphyromonas gingivalis LPS (Journal of Applied Oral Science, 2013)
Objective: The aim of this study was to compare the production of the chemokines CCL3 and CXCL12 by cultured dental pulp fibroblasts from permanent (PDPF) and deciduous (DDPF) teeth under stimulation by Porphyromonas gingivalis LPS (PgLPS). Material and Methods: Primary culture of fibroblasts from permanent (n=3) and deciduous (n=2) teeth were established using an explant technique. After the fourth passage, fibroblasts were stimulated by increasing concentrations of PgLPS (0 – 10 µg/mL) at 1, 6 and 24 h. The cells were tested for viability through MTT assay, and production of the chemokines CCL3 and CXCL12 was determined through ELISA. Comparisons among samples were performed using One-way ANOVA for MTT assay and Two-way ANOVA for ELISA results. Results: Cell viability was not affected by the antigen after 24 h of stimulation. PgLPS induced the production of CCL3 by dental pulp fibroblasts at similar levels for both permanent and deciduous pulp fibroblasts. Production of CXCL12, however, was significantly higher for PDPF than DDPF at 1 and 6 h. PgLPS, in turn, downregulated the production of CXCL12 by PDPF but not by DDPF. Conclusion: These data suggest that dental pulp fibroblasts from permanent and deciduous teeth may present a differential behavior under PgLPS stimulation.